THE COMPARATIVE ANALYSIS OF RADAR-TRACKING SEARCHERS BASED ON NEIMAN-PIERSON CRITERION AND SEQUENTIAL PROBABILITY RATIO TEST - A. S. Khramenkov; S. N. Yarmolik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Use capability the sequential probability ratio test for radar detection is consider. Necessary conditions for comparison Neiman-Pierson criterion and sequential probability ratio test are given.